Development of Thermo-responsive materials for pancreatic cancer management - ElSherbeny, Amr Moustafa Said Moustafa (2024)
Pancreatic cancer, characterised by a high mortality rate and unfavourable prognosis, encounters challenges related to poor therapeutic agent accumulation at the target site, attributed to compromised vascularity and dense desmoplastic stromal layers. Addressing these limitations, stimuli-responsive nanomaterials have emerged as a potential solution. Chapter 1 provides a comprehensive background on pancreatic cancer and discusses the barriers presented by the tumour microenvironment in conventional management techniques. The focus shifts to thermo-responsive micellar-based materials as advanced tools for managing pancreatic cancer, exploring their potential for both local and systemic delivery. The objective of this work is to develop local and systemic thermo-responsive micellar-based systems as effective techniques for treating pancreatic cancer, aiming to advance precision and efficacy in pancreatic cancer treatment. In Chapter 2 of this study, the design of mPEG-PLA-PCL-PLA-mPEG (PELCLE) pentablock polymers, a modification of the commonly used mPEG-PCL-mPEG (PECE) hydrogels found in the literature, was introduced for the local delivery of chemotherapeutic agents in pancreatic cancer management. These amphiphilic thermo-responsive-micellar hydrogels possessed properties that were liquid (sol) at room temperature, allowing for local injection. Upon reaching the tumour site, the hydrogel underwent a phase transition to a gel state at body temperature through micellar coupling, forming networks that enabled sustained drug delivery. The incorporation of poly(D,L-Lactide) (PLA) into these hydrogels was intended to enhance biodegradability and prolong drug release, particularly for hydrophilic agents. PELCLE hydrogels exhibited sustained thermo-responsive behaviour, with reduced micellar size and lower storage modulus, complex viscosity, and porosity compared to PECE. The introduction of PLA contributed to increased hydrolytic biodegradation. Both hydrogels followed similar drug release mechanisms, predominantly adhering to Higuchi and Korsmeyer-Peppas models, with PELCLE almost consistently demonstrating a slower drug release rate. The biocompatibility of PELCLE was confirmed in vitro on PANC-1 cells and in vivo in PANC-1 xenograft subcutaneous mice models. Moreover, PELCLE proved its capability to sustain the release of the fluorescent Cyanin5.5.alkyne (Cy5.5) over two weeks, showcasing higher tumour retention compared to the free Cy5.5. In Chapter 3, our exploration shifted towards integrating conventional chemotherapy used in pancreatic cancer treatment into PELCLE hydrogels. Within this context, gemcitabine HCL (GEM) and oxaliplatin (OXA) combination therapy (GEMOX) were introduced into mPEG-PLA-PCL-PLA-mPEG (PELCLE) pentablock hydrogels, establishing a localised sustained drug delivery system for pancreatic cancer management. Introduction of GEMOX into PELCLE did not significantly alter the mechanical and rheological properties of the hydrogel, ensuring the maintenance of its structural integrity. A sustained drug release profile for GEM and OXA was observed from the PELCLE hydrogels over a period of 2 weeks. Furthermore, the synergistic therapeutic potential of free GEMOX was confirmed by a combination index (CI) below 1 after 72 hours, emphasizing its promising efficacy. Mice subjected to doses of 50 mg/mL GEM and 5 mg/mL OXA tolerated the treatment well, with no observed weight changes or behavioural alterations. However, inconclusive cytotoxic results occurred, as tumour growth remained absent even in the control normal saline group. This limitation hindered a comprehensive understanding of the cytotoxic activity of GEMOX in mice throughout the study period. As such, further studies are still required to confirm whether GEMOX-PELCLE hydrogels may be an alternative therapy for locally advanced pancreatic cancer management. In terms of metastatic pancreatic cancer, a more comprehensive therapeutic approach involving systemic interventions is required. The use of nanoparticle (NP) drug delivery systems emerges as a promising solution, allowing co-formulation of multiple drugs within a single NP platform. In Chapter 4, a novel thermo-responsive urethane core coupled terpolymer was developed from a symmetrical core-carboxylic acid functionalised methoxypolyethyleneglycol-poly(D,L lactide)-co-4-pentynoic acid modified caprolactone triblock terpolymer. Here, carboxylic acid groups were incorporated into one of the blocks of these co-polymers stabilizing the particles against flocculation through partial charge-charge repulsion. Simultaneously, it enhanced interactions with GEMOX, allowing for a higher % drug loading capacity achieving 20% for GEM and 18.5% for OXA. The drug-loaded NPs exhibited a significant reduction in metabolic activity in PANC-1 and MIA PaCa-2 cell lines, inducing increased apoptosis, particularly in the late apoptotic phase whilst revealing time-dependent NP uptake and lysosomal co-localisation. Further studies in 3D PANC-1 mono- and co-culture spheroids, including pancreatic stellate cells, demonstrated penetration and cellular internalisation deep into both spheroid types. In vitro 3D efficacy assays demonstrated that combination drug-loaded NPs and free agents exhibited similar effects on measured cell metabolic activities. However, a more significant decrease in spheroid volume was evident for the combination NPs compared to the free drug combinations in both mono- and co-culture spheroids. These findings underscore the potential of this system as an alternative therapeutic approach for pancreatic cancer management. The study introduced a simple and efficient method for encapsulating hydrophilic chemotherapeutic agents in a thermo-responsive and biodegradable matrix, demonstrating effective delivery in both 2D and 3D pancreatic cancer models.